ANALISIS KEBIJAKAN PENANGANAN STUNTING DI NAGARI KOTO NAN TIGO IV KOTO HILIE KECAMATAN BATANG KAPAS KABUPATEN PESISIR SELATAN PROVINSI SUMATERA BARAT - gusni, nodi hendra; Afifah, Dian Fitriani (Universitas Muhammadiyah Lampung, 2026)
Stunting is a multidimensional public health problem with long-term implications for the quality of human resources, economic productivity, and the sustainability of regional development. In Indonesia, although various national policies have accelerated the reduction in stunting prevalence, regional disparities remain a serious challenge, particularly at the lowest levels of government, such as villages or nagari (village-based villages). This study aims to analyze the implementation of stunting management policies in Nagari Koto Nan Tigo IV Koto Hilie, Batang Kapas District, Pesisir Selatan Regency, with an emphasis on program implementation, cross-sectoral coordination, the role of local institutions, and human resource capacity at the nagari level. The research approach used was a case study with qualitative methods based on document analysis and secondary data, including local government reports, stunting prevalence data at the district and sub-district levels, and documentation of nagari activities. The analysis results indicate that the nagari has implemented a number of local initiatives such as nutrition posts, stunting discussions, and outreach activities, reflecting a commitment to local-level policies. However, the effectiveness of policy implementation still faces various obstacles, including limited integrated by-name-by-address data, uneven capacity of integrated health post (Posyandu) cadres, limited budget support, and the influence of structural factors such as poverty and family parenting patterns. This study confirms that the success of stunting management policies at the village level is determined not only by the existence of the program, but also by the quality of governance, data integration, and the sustainability of cross-sectoral interventions. Therefore, strengthening village institutional capacity, integrating e-PPGBM data into development planning, and a sustainable multisectoral approach are essential prerequisites for accelerating stunting reduction in rural areas.